A Spontaneous Arterial Venous Fistula in a Patient on Hemodialysis: Case Report - Getasew Kassaw Alemu; Addisu Melkie Ejigu; Beniam Yohannes Kassa (Clinical Case Reports)
ABSTRACT Arteriovenous fistula is an abnormal connection between arteries and veins occurring usually following surgery, trauma, catheterization, or local procedures. Spontaneous arteriovenous fistulas are a rare clinical entity with very few cases reported in the literature with unclear mechanisms. We present a case report of a 54‐year‐old Ethiopian female with known chronic kidney disease on hemodialysis for 2 years thrice a week who presented with progressive pulsatile right thigh mass of 7 months duration in the absence of trauma, catheter insertion previously, or surgery. The arteriovenous fistula was confirmed by computed tomography angiography and it was intervened with open surgery with no complication.